Our Experience in the Management of Traumatic Wound Myiasis: Report of 3 Cases and Review of the Literature. (12th October 2016) - Shukla, Anand Deep; Kamath, Abhay T.; Kudva, Adarsh; Pai, Deepika; Patel, Nilesh
Abstract : Compromised health and hygiene can lead to many complications and one among them is traumatic wound myiasis. Myiasis is the invasion of living tissues by larvae of flies. Three cases of traumatic orofacial wound myiasis and treatment strategies followed for the management of them are reported in this paper.